Chapter 31 Central Immune Senescence, Reversal Potentials - Kvell, Krisztian (InTechOpen, 2012)
Ageing is a complex process that affects all living organisms. Senescence is not only conceivable in multicellular organisms, but also in unicellulars. Unlike certain diseases that have specific morbidity rates, ageing is a physiological process that affects all individuals that live long enough (unaffected by i.e. predation or famine) to experience senescence.